The use of digital technologies in teaching about inequalities - Papp Gabriella; Пап Габріелла; Pista Ádám; Пішто Адам (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. Digital technologies play a crucial role in the teaching of mathematical inequalities, as they are capable of bridging the gap between abstract algebraic notations and concrete visual representations. Students often face cognitive difficulties when they must interpret the solution of an inequality in a coordinate system. Dynamic geometry software, such as GeoGebra, provides an interactive learning environment that enables the bridging of this conceptual gap and the development of a deeper understanding. These tools provide immediate, real-time visual feedback, enabling students to actively explore the half-planes that represent the solution set. The present pedagogical research aims to develop and investigate the impact of technologysupported instruction. The study will be conducted among 9th-grade secondary school students while covering the curriculum unit on inequalities and systems of inequalities. The intervention is centered on the purposeful application of the GeoGebra software, which we integrate into the mathematics lessons we conduct, for solving targeted tasks. We place particular emphasis on displaying the solution set of systems of inequalities as a visually interpretable intersection region (feasible region). Our assumption is that this interactive, visual approach significantly increases the students' intrinsic motivation towards the topic. This study contributes to the identification of pedagogical practices that most effectively support the integration of algebraic and geometric thinking in 9th-grade students.
Keywords: mathematics education; digital technologies; inequalities